2017
DOI: 10.1186/s12967-017-1206-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of H2S during acute bacterial infection: a review

Abstract: Hydrogen sulfide (H2S), previously only considered a toxic environmental air pollutant, is now increasingly recognized as an important signaling molecule able to modulate several cellular pathways in many human tissues. As demonstrated in recent studies, H2S is produced endogenously in response to different cellular stimuli and plays different roles in controlling a number of physiological responses. The precise role of H2S in inflammation is still largely unknown. In particular, the role of H2S in the regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 97 publications
1
52
0
Order By: Relevance
“…Robles‐Vera et al found that rats who received l ‐NAME had higher mRNA levels of IFN‐γ, which is produced by T helper‐1 cells infiltrating the aorta. Benedetti et al reported that IFN‐γ is responsible for the structural and haemodynamic changes in hypertension and that its deficiency resulted in the attenuation of hypertension.…”
Section: Discussionsupporting
confidence: 90%
“…Robles‐Vera et al found that rats who received l ‐NAME had higher mRNA levels of IFN‐γ, which is produced by T helper‐1 cells infiltrating the aorta. Benedetti et al reported that IFN‐γ is responsible for the structural and haemodynamic changes in hypertension and that its deficiency resulted in the attenuation of hypertension.…”
Section: Discussionsupporting
confidence: 90%
“…H 2 S was found to inhibit the induction of an inflammatory response on infection with Mycoplasma fermentans . Underlying mechanism revealed that H 2 S inhibited the activation and nuclear translocation of a redox sensitive transcription factor NF‐κB, thereby diminishing the transcription of proinflammatory genes . One of the mechanism by which H 2 S affects the activity of a global transcriptional regulator, NF‐κB, is by persulfidation of Cys‐38 residue in the p65 subunit .…”
Section: H2s and Host–pathogen Interactionmentioning
confidence: 99%
“…The variation in mycoplasma lipoproteins attributed to genome rearrangements and genetic insertions have been demonstrated to lead to phenotypic plasticity that allows also for the evasion of the host's defense system and pathogenesis [13][14][15]. Some strains of mycoplasma can invade intracellularly [16][17][18], including Mycoplasma fermentans [19], enhancing their ability to evade the immune system [20]. Given their presence on mostly mucosal surfaces (respiratory and urogenital tracts, eyes, alimentary canal, mammary glands and joints [21][22][23]), mycoplasmas have been associated to respiratory [24,25], urogenital [26][27][28] and rheumatoid diseases [29][30][31].…”
Section: Introductionmentioning
confidence: 99%